2005
DOI: 10.1101/gad.1253805
|View full text |Cite
|
Sign up to set email alerts
|

Premature targeting of a cell division protein to midcell allows dissection of divisome assembly in Escherichia coli

Abstract: Cell division in Escherichia coli requires the recruitment of at least 10 essential proteins to the bacterial midcell. Recruitment of these proteins follows a largely linear dependency pathway in which depletion of one cell division protein leads to the absence from the division site of "downstream" proteins in the pathway. Analysis of events that underlie this pathway is complicated by the fact that a protein's ability to recruit "downstream" proteins is dependent on its own recruitment by "upstream" proteins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
131
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 129 publications
(139 citation statements)
references
References 39 publications
7
131
1
Order By: Relevance
“…This ordinarily means that old peptidoglycan is not degraded unless the divisome is functioning properly. Consistent with previous studies suggesting a role for FtsN in activation of the divisome and initiation of septation and separation of daughter cells (5,(26)(27)(28), our results suggest that recruitment of FtsN functions to ensure that cell wall degradation does not take place unless new cell wall is being incorporated at the emergent poles. Also consistent with a regulatory rather than, for instance, an essential enzymatic role, mutants that are missing FtsN can be suppressed by mutations in another component of the divisome, FtsA (29).…”
Section: Discussionsupporting
confidence: 81%
“…This ordinarily means that old peptidoglycan is not degraded unless the divisome is functioning properly. Consistent with previous studies suggesting a role for FtsN in activation of the divisome and initiation of septation and separation of daughter cells (5,(26)(27)(28), our results suggest that recruitment of FtsN functions to ensure that cell wall degradation does not take place unless new cell wall is being incorporated at the emergent poles. Also consistent with a regulatory rather than, for instance, an essential enzymatic role, mutants that are missing FtsN can be suppressed by mutations in another component of the divisome, FtsA (29).…”
Section: Discussionsupporting
confidence: 81%
“…The latter two proteins are predicted to be transpeptidases involved in peptidoglycan cross-linking during septum synthesis (12,14). FtsQ is an integral part of the divisome and is believed to play a crucial role in the recruitment of early and late cell division proteins and peptidoglycan polymerases (4,23,51). Our studies showed increased GFP-FtsI MT localization at the septa and enhanced Bocillin-FL staining under conditions of CrgA overproduction.…”
Section: Discussionmentioning
confidence: 99%
“…FtsQ can co-purify with its downstream partners FtsL and FtsB 87 . Moreover, when targeted prematurely to the Z ring by fusion to ZapA, FtsQ can recruit FtsL, FtsB and the later protein FtsI (but not FtsN) to the Z ring in the absence of the upstream proteins FtsW or FtsA 88 . The failure of FtsN to be recruited in this system indicates that the proper assembly of all components at the septum, particularly FtsA, might be essential for the localization of FtsN.…”
Section: Ftsz Function In Bacteria Assembly Of the Cytokinesis Machinementioning
confidence: 99%